2014
DOI: 10.1021/la502965q
|View full text |Cite
|
Sign up to set email alerts
|

Rough Glass Surface-Mediated Formation of Vesicles from Lauryl Sulfobetaine Micellar Solutions

Abstract: We report novel vesicles composed of the zwitterionic surfactant lauryl sulfobetaine (LSB), which is a simple single-tailed surfactant (STS). The novel vesicles spontaneously formed from LSB micellar solutions with the mediation of a rough glass surface (RGS) in the absence of any cosurfactants or additives. Importantly, the obtained STS vesicles displayed good stability upon long-term storage, exposure to high temperature, and freeze-thawing after the RGS was removed. The pH of the LSB solution (4.0-9.0) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Commonly, simple STAs, such as sodium dodecyl sulfate (SDS) and sodium dodecylbenzenesulfonate (SDBS), are considered to be unable to form vesicles in aqueous solution in the absence of cosurfactants or any other additives, even in chemical textbooks . More recently, we found an interesting phenomenon that rough glass surfaces can promote an STA spontaneously forming vesicles without any additives. , This inspired us to explore the probability of STA vesicle formation mediated by clay mineral surfaces, which played an active role in the abiotic origin of life …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly, simple STAs, such as sodium dodecyl sulfate (SDS) and sodium dodecylbenzenesulfonate (SDBS), are considered to be unable to form vesicles in aqueous solution in the absence of cosurfactants or any other additives, even in chemical textbooks . More recently, we found an interesting phenomenon that rough glass surfaces can promote an STA spontaneously forming vesicles without any additives. , This inspired us to explore the probability of STA vesicle formation mediated by clay mineral surfaces, which played an active role in the abiotic origin of life …”
Section: Introductionmentioning
confidence: 99%
“…18 More recently, we found an interesting phenomenon that rough glass surfaces can promote an STA spontaneously forming vesicles without any additives. 19,20 This inspired us to explore the probability of STA vesicle formation mediated by clay mineral surfaces, which played an active role in the abiotic origin of life. 21 In this work, we chose two common anionic STAs, SDS and SDBS, as model constituents of early membranes rather than fatty acids, to establish a tentative model for protocell structures.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no obvious change in the appearance of vesiclesolutions was observed before and after heating at 80 1C for 2 h. These results indicate the remarkable stability of C n TAB vesicles, similar to our previous results on the vesicles of STAs. [25][26][27][28][29][30]33 3.4 Possible mechanism for DHRH-induced micelle-to-vesicle transition Based on the above results, it can be concluded that, using a DHRH process, the micelle-to-vesicle transition occurs for C n TABs in their single-component solutions (without any additives). For TTAB and CTAB, a complete transition from micelles…”
Section: Stability Of C N Tab Vesiclesmentioning
confidence: 85%
“…to vesicles can be achieved, forming pure vesicle systems, while for DTAB, only a partial transition occurs, forming a vesicle/ micelle coexisting system. In our previous reports, 25,26,28,30 it was demonstrated that RGSs can in situ mediate the micelle-to-vesicle transition for STAs in water, but smooth glass plates cannot. A possible mechanism for the RGS-mediated micelle-to-vesicle transition was proposed: 25 STA micelles and molecules adsorb on the RGSs to form curved bilayers, which are closed to form vesicles when detached from the RGSs.…”
Section: Soft Matter Papermentioning
confidence: 99%
See 1 more Smart Citation